Status of groundwater and river water quality around the location of illegal gold mining activities in Lantung District, Sumbawa - Kevin Philips Barakati; Tjahyo Nugroho Adji; Noorhadi Rahardjo (Brawijaya University, 2023)
The Lantung area is one of the places on Sumbawa Island with a large gold deposit. One of the activities of the Lantung people that has the potential to damage the environment is separating gold from mercury. This study aimed to examine the activity of the gold laundering process, and the level of contamination of groundwater and river water due to gold processing from amalgamation by mercury (Hg+) waste. In this study, sampling was carried out for each location, namely two samples of wastewater, six samples of river water, and two samples of groundwater, which were then tested in the laboratory on the parameters of mercury and TSS. At the same time, pH was measured in the field. Furthermore, from the survey results, it was found that the use of mercury was ±150-250 mL at each gold processing location. The results showed that all samples from wastewater (tailings), groundwater and river water were contaminated with mercury with levels exceeding the acceptable quality standards. Furthermore, the status of water quality using the Pollution Index (IP) method shows that wastewater is light to moderately polluted, groundwater is lightly polluted, and river water is also lightly to moderately polluted.